The tobacco epidemic – pharmacological interventions for smoking cessation - Sergiel, Natalia; Maj, Patrycja; Włodarczyk-Cybulska, Karolina; Kania, Agata; Gonet, Malwina; Miszczyk, Karolina; Serwik-Trandasir, Aleksandra; Mozer, Piotr; Maternia, Jakub; Lazar, Michał (Journal of Education, Health and Sport, 2023)
Introduction: One of the biggest public health threats in the world is tobacco epidemic. According to WHO in the world cigarette smoking is the most common form of tobacco use. In the 2018 report of the World Health Organization (WHO), smoking was recognized as one of the main risk factors responsible for premature mortality due to non-communicable diseases. According to the Global Burden of Disease, estimates smoking causes almost 8 million deaths in 2019 worldwide. In Poland about one-quarter of adults smoke cigarettes. As a result, scientists are constantly looking for medications that could help people quit smoking. The aim of the study: The aim of our study is to present medication which are used for treating nicotine dependence nowadays. Moreover, we give attention to social and economic consequences of tobacco use. Materials and methods: The literature available on PubMed and Google Scholar was reviewed using the words: “smoking”, “smoking cessation”, “nicotine”, “nicotine replacement therapy”. Description of the state of knowledge: Exposure to tobacco smoke is a dominant factor in the incidence of many cancers as well as cardiovascular and respiratory diseases. Therefore, improving smoking cessation interventions is critical to reducing tobacco use and helping to minimize the burden of cancer and other diseases for example chronic obstructive pulmonary disease. Conclusions: Smoking cessation has a positive effect on health. Nicotine replacement therapy, Bupropion, Varenicline and Cytisine are used to reduce nicotine withdrawal symptoms in regular smokers who abstain from smoking.